ANALISIS PENGARUH PERILAKU PEMIMPIN DAN KOMITMEN KARYAWAN TERHADAP PRESTASI KERJA KARYAWAN - Jessica, Jessica; Hartomo, Eric; Simanjuntak, Demak Claudia Yosephine; Pulungan, Delyanti A. (Aksara Public, 2019)
This study aims to examine and analyze the influence of leader behavior and employee commitment to employee performance at PT Motorindo Perkasa Raya. This research use the 71 employees who come from PT Motorindo Perkasa Kingdom as research samples. Data collection conducted in research using questionnaire techniques with questionnaires, and interviews using interview sheets. Questionnaires are given to employees to find out perceptions about variable leader behavior, employee commitment and work performance of employees. Interviews were conducted on 3 employees and 1 leader to find out more symptoms related to leader behavior, employee commitment and employee performance variables. The data analysis model used in the study is a multiple linear regression analysis model. Based on the results of the study partially showed that the leader behavior variable and employee commitment had a positive and significant effect on employee work performance at PT. Motorindo Perkasa Raya. While the results of testing simultaneously show that leader behavior and employee commitment have a positive and significant effect on employee performance at PT. Motorindo Perkasa Raya.